Restructuring through spinoffs - Cusatis, Patrick J.; Miles, James A.; Woolridge, J.Randall (Journal of Financial Economics, 1993)
We investigate the value created through spinoffs over the 1965–1988 period by measuring the stock returns of spinoffs, their parent firms, and parent-spinoff combinations for periods of up to three years following the spinoffs. We find significantly positive abnormal returns for spinoffs, their parents, and the spinoff-parent combinations. Both the spinoffs and parents experience an unusually high incidence of takeovers and the abnormal performance is limited to firms involved in takeover activity. These findings suggest that spinoffs provide a low-cost method of transferring control of corporate assets to bidders who will create greater value.